Students’Experiential Learning of Hydroponics and Local Markets on the Island of Roatán, Honduras - Lori Unruh Synder; Michael V. Micklebart; Val Eylands (Journal of International Agricultural and Extension Education, 2012)
International experiences for students provide a means for globalization of higher education, promoting communication and understanding of real world issues. Undergraduatestudents participating in a 10-day short course study abroad to Honduras experienced first-hand entrepreneurial education by working directly with a farm business while learning applied science of water and light relations with regard to hydroponically grown plants on the island of Roatán. This paper describes the teaching methods the professors implemented in order to help improve students’ understanding of complexissues related to science. Undergraduate students worked in pairs to collect greenhouse data and helped to harvest and package lettuce and mint to sell to local markets. The students were given a pre-test about water and light relations and were asked to respond to questions about issues they might encounter related to plant water uptake within a tropical greenhouse setting. The students participated in reflective sessions with the business owner after work experience, followed by post-tests after completing the exercises. These teaching methods were repeated for two years with a total of 20 participants. Overall, the post-test scores showed a gain in science knowledge. During reflective sessions, students commented that they enjoyed this unique mini-research experience and felt it was more valuable than just touring. Students appreciated the comprehensive interactions with the agricultural business and gained self-awareness related to entrepreneurship in agriculture. Study-abroad courses should try to include hands-on experiences for students to engage with local entrepreneurs and to apply science-based questions to promote critical thinking skills
Keywords: Entrepreneurship; Greenhouse; Honduras; Hydroponics; Lettuce; Study Abroad; Tropical Agriculture